Perencanaan Strategi Pemasaran Kerajinan Kayu untuk Meningkatkan Volume Penjualan Menggunakan Analisis SWOT dan QSPM - Viki Uswatul Khoridah; Anita Oktaviana Trisna Devi; Erna Indrianingsih (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
SMEs play an important role in Indonesia's economy, one of which is the woodcraft industry that has great potential for export. Putra Mandiri Woodcraft (PMW) faces sales instability, ranging from 30% to 145.48% of the set target, which affects production efficiency. This study aims to formulate an effective marketing strategy to increase sales volume and business competitiveness. The methods used in this study include the IFE and EFE Matrix analysis to identify internal and external factors affecting the company, SWOT analysis to formulate various strategies, and QSPM to determine strategy priorities based on the Total Attractiveness Score (TAS) value. The analysis results show that Putra Mandiri Woodcraft has an IFE score of 2.70 and an EFE score of 2.80, indicating that the company's internal condition is quite strong, although the response to external factors is still moderate. The company's main strengths lie in product quality and consumer trust, while its weaknesses are the lack of innovation in product design. Based on the SWOT analysis results, eight potential strategies were found, and the QSPM shows that expansion through a marketplace based on product quality and more varied designs is the main priority with a TAS value of 6.16.